(untitled) (Malaysian Management Journal, 2009)
Knowledge sharing is one important activity in knowledge management. It enables knowledge to be created, as well as acquired and used by others. However, there are reasons to believe that employees are reluctant to share knowledge with their colleagues. Thus, in order to ensure the success of knowledge management effort, knowledge sharing among employees must be encouraged. Though studies had shown that there are many factors that might affect knowledge sharing behaviour, this paper aims at exploring the relationship between organizational commitment and knowledge sharing behaviour. Regression analysis on data gathered from a sample of 114 R&D employees’ indicated that affective commitment and normative commitment were significant predictors of tacit knowledge sharing. Additionally, explicit knowledge sharing was significantly and positively predicted by affective commitment. Implications, limitations, and suggestions for future research are highlighted.